Dysphoric milk ejection reflex as a new diagnostic and therapeutic challenge in lactation care - literature review - Katarzyna Skowrońska; Anna Chmura; Patrycja Baciur; Agnieszka Środoń (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Breastfeeding has many health benefits. The guidelines recommend breastfeeding up to 6 months of age. Many mothers stop breastfeeding early, one reason being the dysphoric ejection reflex (D-MER). It is a negative emotional reaction related to the ejection of milk.